Launch of the first canine mobile blood donation center in Asia: development, outcomes, and influence of an animal bloodmobile - Choi, Hee-Jae; Han, Hyun-Jung (Frontiers in Veterinary Science, 2024)
A mobile blood donation station allows a maximum number of donors to donate blood at any location. In veterinary medicine, no previous studies have reported the use of bloodmobiles for blood donation in animals. We assessed Asia's first canine mobile blood donation center, which was trialed using a modified vehicle in South Korea. The bloodmobile visited 12 locations nationwide. Of the 750 applicants, 48 donor dogs were selected for investigation. Ten failed to donate blood owing to the following issues: behavioral problems (2/48), positive results on vector-borne disease screening tests (5/48), in-tubing clot formation (2/48), and absence on the relevant appointment date (1/48). Blood collection took approximately 12 minutes, and the entire procedure lasted an average of 1.5 hours per donor. The prevalence rates of dog erythrocyte antigen 1-negative and 1-positive blood were 32.6% and 67.4%, respectively. There were no donation-related complications, except for one dog that had contact dermatitis induced by clipper irritation. The post-donation survey completed by 46 owners revealed that most were satisfied with the campaign. The convenience of the mobile blood drive (93.5%) was a key factor contributing to high owner satisfaction and willingness to participate in future campaigns (95.7%), in line with findings from prior veterinary and human blood donation motivation research. The initiative effectively increased engagement in canine blood donation by enhancing accessibility. To optimize canine mobile blood drives, procuring larger vehicles and enhancing infrastructure for future campaigns would be beneficial. In conclusion, this study showed that Asia's first canine bloodmobile was successful in terms of improving the convenience, accessibility, and efficacy of canine blood donation. Although the concept is still unfamiliar to the public, active promotion of canine blood donation can help ensure a robust blood donation culture in the veterinary field.